Bloomland : a novel - Englehardt, John, 1987- (Dzanc Books, 2019)
In this richly textured debut, John Englehardt explores how the origin and aftermath of the shooting impacts the lives of three characters: a disillusioned student, a grieving professor, and a young man whose valuation of fear and disconnection funnels him into the role of the aggressor. As the community wrestles with the fallout, Bloomland interrogates social and cultural dysfunction in a nation where mass violence has become all too familiar.